The Influence of Self Service Technology (SST) on Customer Satisfaction of Digital Services Users at Indonesia Islamic Bank - Febry Nabila Syahrani; Aqwa Nasser Daulay; Nurbaiti Nurbaiti (Airlangga Journal of Innovation Management, 2023)
This research aims to analyze the effect of Self-Service Technology on customer satisfaction of digital service users at Indonesia Islamic Bank especially BSI KCP Kisaran. BSI KCP Kisaran Self-Service Technology consists of Automatic Teller Machine (ATM), internet banking, and mobile banking. This research also analyze how is the influence of these three SST facilities simultaneously on customer satisfaction. This research uses a quantitative approach with multiple linear regression analysis. Research data sources use primary and secondary data. According to the results of data analysis shows that ATM has a significant effect on customer satisfaction. In other side, internet banking and mobile banking also have a significant effect on customer satisfaction. Based on results found that customers still experience high benefits from transaction by ATM, internet banking, and mobile banking. These results indicate that customers are satisfied within BSI KCP Kisaran Self-Service Technology that consists of ATM, internet banking, and mobile banking. This study bring an implication that the optimizing Self-Service Technology would increase the Islamic Bank customer satisfaction.